The Quality Improvement Assistantship Program for Madrasa Education in Mindanao, the Philippines - Muhlisin, Muhlisin; Sofi, Muhammad Jauhari; Shobirin, Ma’as; Deporos, Saprolla Rollie C. (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
Madrasa education is a compelling issue in a Muslim minority country like the Philippines. Amidst the rapid pace of modernization, secular education enjoys strong government support, while Islamic teaching often remains underemphasized. However, the madrasa education system in the Philippines has begun to make positive strides through mutual learning and exchanging experiences with neighboring countries, such as Indonesia. Likewise, the present intensive and participatory assistantship program aimed to elucidate the efforts to promote religious moderation and enhance the educational quality within selected madrasas in Mindanao, the Philippines. The Participatory Action Research (PAR) method, combined with direct mentoring, was employed in this endeavor. Furthermore, the program was designed to address three key objectives: (1) strengthening religious moderation within madrasa education, (2) preparing professional teachers for madrasa education, and (3) enhancing the management of madrasa education. In summary, the outcomes of this program have the potential to contribute to the adoption of the Indonesian Islamic education model within the Muslim community in the Philippines.